Peranan Sarawak Tourism Board dalam mempromosikan Rainforest World Music festival 2005 kepada masyarakat umum di Sarawak - Md. Deni, Zuraidah (Universiti Malaysia Sarawak (UNIMAS), 2006)
The Rainforest World Music Festival (RWMF) which is held at the Sarawak Cultural Village has become a truly international music event, attracting performers and ethnic music lovers from all corners of the world. Promotion is an important element in introducing and attracting tourists to participate in this festival. This research examines the role of the Sarawak Tourism Board in promoting RWMF to the public.